Measuring The Level Of Mixed-Use And Compactness Of Gottera Condominium Site In Addis Ababa, Ethiopia - Kalkidan Ketema (ASTU, 2021)
Compactness/ Compact Development Is One Of The Recent Concepts On Achieving Sustainability In Urban Planning. It Is Characterized By Three Classifications Is Into Economic Density, Morphological Density And Mixed Land. And Its Positive Implication On Urban Development Is Obtained Through Sustainable Transport Mode, Improved Service Access, Lower Crime Rates, Social Equity, A Higher Value Of Space, Shorter Trip Length, Lower Energy Consumption And More Efficient Division Of Local Public Services. And It Is Also Expected To Have A Negative Implication On The Absence Of Greenery And Open Space And Other Health-Wise Effects It Might Bring. In This Paper The Practice Of Compact City Development Is Discussed On Cities In Developing Countries With Low Income Like Addis Ababa, Ethiopia. The Conditions In The Gottera Condominium Are Discussed To Answer The Research Questions How Mixed And Compact Is Gottera Condominium? What Are The Evaluation Variables For Compact Development And Mixed Use And What Are The Mechanism To Practice The Best Mixed Use And Compact Development? Using The Mixed Methodology For Gathered Data And Analysis Findings Are Indicated That The Gottera Condominium Has Fulfilled Some Requirements Of Compact Development And Mixed Use Like Walkability, Density, Mixed Uses And Other concepts That Make A Neighborhood Sustainable.
Keywords: compact development, condominium, mixed-use, sustainability, urban development.